Study on the Method of the Self-adapting Image Threshold Divided in the Surface Image of the Tubular Cartridge Case - Wu Qizhou; Jin Yong; Wang Liming (Institute of Advanced Engineering and Science, 2013)
The technology of detecting the internal and external diameter of the tubular cartridge case that using scanistor to obtain the image of the tubular cartridge case surface, aiming at the difference in the image of the surface between the degree of color gray. This article proposed the self-adapting image threshold divided method that base on mean and standard difference of the image of the surface using to definition threshold, solved the key question of the surface image manipulation, make the detecting result reaching the upper precision. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3581